The effects of injury and illness on haemoglobin mass - Gough, C. E.; Sharpe, K.; Garvican, L. A.; Anson, J. M.; Saunders, P. U.; Gore, C. J. (International Journal of Sports Medicine, 2013)
This study sought to quantify the effects of reduced training, surgery and changes in body mass on haemoglobin mass (Hbmass) in athletes. Hbmass of 15 athletes (6 males, 9 females) was measured 9±6 (mean±SD) times over 162±198 days, during reduced training following injury or illness. Additionally, body mass (n=15 athletes) and episodes of altitude training (n=2), iron supplementation (n=5), or surgery (n=3) were documented. Training was recorded and compared with pre-injury levels. Analysis used linear mixed models for ln(Hbmass), with Sex, Altitude, Surgery, Iron, Training and log(Body Mass) as fixed effects, and Athlete as a fixed and random effect. Reduced training and surgery led to 2.3% (p=0.02) and 2.7% (p=0.04) decreases in Hbmass, respectively. Altitude and iron increased Hbmass by 2.4% (p=0.03) and 4.2% (p=0.05), respectively. The effect of changes in body mass on Hbmass was not statistically significant (p=0.435).The estimates for the effects of surgery and altitude on Hbmass should be confirmed by future research using a larger sample of athletes. These estimates could be used to inform the judgements of experts examining athlete biological passports, improving their interpretation of Hbmass perturbations, which athletes claim are related to injury, thereby protecting innocent athletes from unfair sanctioning.